Soviet “Life Canon” in scientist’s biography and problem of its overcoming (Proceedings of Southern Federal University. Philology, 2015)
This article is dedicated to one of the fragments of modern textual culture, namely the presentation of the image of the scientist, usually presented in the book, devoted to anniversaries. Often it is the memories of students. Scientific pathos of the article is due to the fact that these memories do not always create a life image of the scientist, not realizing his appointment. Often different publications not only smooth personal traits of individuals, but also smooth individual features of the style of the authors and individual differences of their texts. The article identifies the causes of these phenomena. One of them is blind, non-functional copy of topos characteristic of Soviet biographies. It is, for example, a topos of poverty and democratic origin of the scientist who during the Soviet biographies was intended to carry out agitation and didactic function. Combining topos with biographical frame results in a maximum leveling in the representation of a person. Thus it appears what the article calls “Soviet life canon.” Another reason for the smoothing of individual style and create a speculative form of teaching is the penetration in the biographical genre of officialese expressing indifferent attitude to people. Concerning modern biographies of scientists officialese involves business style, that serves genres of reviews, i.e. all that is related to business decision-making relating to the work of the scientist. The article pointed out ways to overcome these negative trends in modern publications related to the demand for intimization category, which primarily should be shown in the plot structure of the narration.Keywords: life, biography, scientist, frame, topos, officialese, intimization.Khazagerov Georgii Georgievich - Ph. D., professor of the Russian language dpt. Institute of linguistics, journalism and cross-cultural communication of Southern Federal University, Rostov-on-Don, Russian Federation. Ph.: 8-863-263-42-28.Scharenskaya Nataliya Markovna - professor of the Russian language dpt. Institute of linguistics, journalism and cross-cultural communication of Southern Federal University, Rostov-on-Don, Russian Federation. Ph.: 8-918-511-48-86. E-mail: n-scharenskaja@yandex.ru